Regional Price Adjustment in a Monetary Union - Jan Marc Berk; Job Swank (Tinbergen Institute, 2002)
Using a New-Keynesian framework, we investigate how far the inflationary processes in member states of EMU cause regional price levels to converge. We fail to produce hard evidence of the present existence of such an adjustment mechanism, notwithstanding that inflation in some countries tends to converge towards the euro area level. Overa11, inflation persistence has declined significantly over the years, but there are still marked differences between countries on this score. We conclude that the euro area is not an optimal currency area yet, lending support to the quest for further structura1 reforms in European labour and product markets.
Keywords: E31; F02; E58; 330; Inflation; EMU; monetary policy.; Inflation; Entwicklungskonvergenz; Phillips-Kurve; Eurozone; EU-Staaten